The Arrival of the Hero in a Ship: A common Leitmotif in OE Regnal Tables and the Story of Scyld Scefing in Beowulf - Salvador Bello, Mercedes (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen